SHP2 protects endothelial cell barrier through suppressing VE‐cadherin internalization regulated by MET‐ARF1. Issue 1 (13th August 2018) - Zhang, Jie; Huang, Jiaqi; Qi, Tongyun; Huang, Yizhou; Lu, Yuting; Zhan, Tianwei; Gong, Hui; Zhu, Zhengyi; Shi, Yueli; Zhou, Jianhong; Yu, Luyang; Zhang, Xue; et al.
ABSTRACT: Vascular endothelial (VE)–cadherin junctional localization is known to play a central role in vascular development, endothelial barrier integrity, and homeostasis. The sarcoma homology domain containing protein tyrosine phosphatase (SHP)2 has been shown to be involved in regulating endothelial barrier function; however, the mechanisms remain largely unknown. In this work SHP2 knockdown in an HUVEC monolayer increased VE‐cadherin internalization and endothelial barrier permeability. Loss of SHP2 specifically augmented the GTPase activity of ADP‐ribosylation factor (ARF)‐1. ARF1 knockdown or inhibition of its guanine nucleotide exchange factors (GEFs) markedly attenuated VE‐cadherin internalization and barrier hyperpermeability induced by SHP2 deficiency. SHP2 knockdown increased the total and phosphorylated levels of MET, whose activity was necessary for ARF1 activation and VE‐cadherin internalization. Furthermore, constitutive endothelium‐specific deletion of Shp2 in mice led to disrupted endothelial cell junctions, massive hemorrhage, and lethality in embryos. Induced and endothelium‐specific deletion of Shp2 in adult mice resulted in lung hyperpermeability. Inhibitors for ARF1–GEF or MET used in pregnant mice prevented the vascular leakage in endothelial Shp2 ‐deleted embryos. Together, our findings define a novel role of SHP2 in stabilizing junctional VE‐cadherin in the resting endothelial barrier through suppressing MET and ARF1 activation.—Zhang, J., Huang, J., Qi, T., Huang, Y., Lu, Y., Zhan, T., Gong, H., Zhu, Z., Shi, Y., Zhou, J., Yu, L., Zhang, X., Cheng, H., Ke, Y. SHP2 protects endothelial cell barrier through suppressing VE‐cadherin internalization regulated by MET‐ARF1. FASEB J. 33, 1124–1137 (2019). www.fasebj.org